2019
DOI: 10.1158/1940-6207.capr-18-0462
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Epidemiologic Pattern of Precancerous Lesions of Esophageal Squamous Cell Carcinoma in a High-risk Area of Huai'an, Jiangsu Province, China

Abstract: Better understanding of esophageal precancerous lesions (EPL) can inform prevention strategies for esophageal squamous cell carcinoma (ESCC). Here, a cross-sectional epidemiologic study based on the Early Diagnosis and Early Treatment Project of Esophageal Cancer database from 2011 to 2017 was performed to fully investigate and characterize the epidemiology of EPL in rural Huai'an District. Data of 11,518 participants ages 35-75 years were collected through face-to-face interviews by questionnaire. Participant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 40 publications
2
52
1
Order By: Relevance
“…However, the EC incidence was detected equally in both genders (male/female ratio: 1) in this study, which is an important finding. In a recent epidemiological study, Pan et al 34 found that EC is only up to about 1.5-fold more common in men than in women in a rural area, and alcohol/tobacco use play only a minor role, whereas some other factors that influence both sexes equally may take the main responsibility, such as environmental and dietary factors. Therefore, the areas where have high EC incidence may have something in common.…”
Section: Esophageal Cancer (Ec)mentioning
confidence: 99%
“…However, the EC incidence was detected equally in both genders (male/female ratio: 1) in this study, which is an important finding. In a recent epidemiological study, Pan et al 34 found that EC is only up to about 1.5-fold more common in men than in women in a rural area, and alcohol/tobacco use play only a minor role, whereas some other factors that influence both sexes equally may take the main responsibility, such as environmental and dietary factors. Therefore, the areas where have high EC incidence may have something in common.…”
Section: Esophageal Cancer (Ec)mentioning
confidence: 99%
“…It was reported that 24% of mild dysplasia, 50% of moderate dysplasia, and 74% of severe dysplasia would develop ESCC during a 3.5-year period [4]. The primary risk factor that increases the risk of ESCC/EPL in one population may not be significantly associated with this cancer in another, which means that there may be completely different patterns of epidemiology between populations, and the geographic distribution of ESCC/EPL varies greatly [1,5]. In Huai'an District, an endemic region of EC in the Jiangsu Province of East China (Figure 1), the crude incidence and mortality of EC during 2008 and 2012 were 96.15/100,000 and 63.25/100,000, respectively [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported a distinct epidemiological pattern of EPL in Huai'an District and the consumption of alcohol and tobacco products, which has been the key risk factors in many regions. However, these factors only played a minor role in the EPL risk, with other factors such as genetic polymorphism, environmental exposures, and dietary factors reported to take the main responsibility for esophageal carcinogenesis in this endemic region [7][8][9][10]36].…”
Section: Study Subjects and Epl Diagnosismentioning
confidence: 93%
“…The best results of reducing the proportion of cancer patients who are diagnosed at late stages are associated with an early diagnosis, which is commonly known as the "early stages" [3]. Therefore, esophageal squamous dysplasia, which is the recognized esophageal precancerous lesion (EPL) for ESCC, has been of greater interest over the last decade [4][5][6][7][8][9][10]. A previous study indicated that 24% of mild dysplasia, 50% of moderate dysplasia, and 74% of severe dysplasia could develop ESCC during a 3.5-year period [6].…”
Section: Introductionmentioning
confidence: 99%